2019
DOI: 10.22460/pej.v3i2.1284
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Internet-Based Learning Media in Enhancing Science Literacy Capabilities of PGSD Students

Abstract: This study was to determine the effect of the use of internet-based learning media in improving the scientific literacy skills of PGSD students. The method used in this study was pre-experimental with the research design of one group pretest-posttest. The population in this study were all IKIP Siliwangi PGSD students in the fourth semester of regular classes and non-regular classes with a total of 300 students. The sample in the study was regular class students with 38 students. The instruments used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 1 publication
0
14
0
2
Order By: Relevance
“…The previous research findings stated that learning media could make it easier for students to understand learning materials (Abror et al, 2020;Lai & Tai, 2021;Ntobuo et al, 2018). Other research findings also state that learning media can increase student enthusiasm in learning to improve student learning outcomes (Budiarto et al, 2020;Darmaji et al, 2019;Samsudin et al, 2019). It can be concluded that learning media can increase students' learning motivation.…”
Section: Introductionmentioning
confidence: 94%
“…The previous research findings stated that learning media could make it easier for students to understand learning materials (Abror et al, 2020;Lai & Tai, 2021;Ntobuo et al, 2018). Other research findings also state that learning media can increase student enthusiasm in learning to improve student learning outcomes (Budiarto et al, 2020;Darmaji et al, 2019;Samsudin et al, 2019). It can be concluded that learning media can increase students' learning motivation.…”
Section: Introductionmentioning
confidence: 94%
“…The rapid growth of the current world of technology has created many internet-connected applications (Binali et al, 2021;Sugiarto, 2020). Teachers should strengthen these technological advances to help make learning activities successful in the world of learning (Khairunnisa, 2021;Samsudin et al, 2019). It is due to the influence of technology that extends to various fields of life, including education, so from this, it is because the progress of the learning world cannot run without the encouragement of technology (D. N. L. Laksana, 2020;Lu & Wang, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the internet itself is the largest computer network in the world (Faslah, 2011;Samsudin et al, 2019). A computer network means a group of computers linked together so that users can share information and resources (Liang et al, 2011;Zendler & Greiner, 2020).…”
Section: Introductionmentioning
confidence: 99%